Iron-Fur complex suppresses the expression of components of the cyclo-(Phe-Pro)-signaling regulatory pathway in Vibrio vulnificus - Lee, Keun-Woo; Kim, Soyee; Lee, Sora; Kim, Minjeong; Song, Suji; Kim, Kun-Soo (Frontiers in Microbiology, 2023)
In the human pathogen Vibrio vulnificus, the quorum-sensing (QS) signal molecule cyclo-(L-Phenylalanine-L-Proline) (cFP) plays a critical role in triggering a signaling pathway involving the components LeuO-vHUαβ-RpoS-KatG via the membrane signal receptor ToxR.In this study, we investigated the impact of iron on the expression of these signaling components. We found that the transcription of the membrane sensor protein ToxR was not significantly affected by Fur-iron. However, Fur-iron repressed the transcription of genes encoding all the downstream cytoplasmic components in this pathway by binding to the upstream regions of these genes. Consequently, the expression of genes regulated by the alternative sigma factor RpoS, as well as the resistance to hydrogen peroxide conferred by KatG, were repressed. Additionally, we observed that in Vibrio cholerae, genes dependent on ToxR showed higher expression levels in a fur-deletion mutant compared to the wild type.These findings indicate that iron, in association with Fur, represses virtually all the cytoplasmic components responsible for the ToxR-dependent cFP-signaling pathways in these two pathogenic Vibrio species. This study, along with our previous reports demonstrating the repression of components involved in AI-2 dependent QS signaling by Fur-iron, highlights the crucial role of iron in quorum-sensing regulation, which is closely associated with the pathogenicity of this human pathogen.